Experimental Investigation into Electrical Discharge Machining of Stainless Steel 304 - M. M., Rahman; K., Kadirgama; M. M., Noor; R. A., Bakar; M. A. R., Khan (Asian Network for Scientific Information, 2011)
This study presents the experimental investigation of the machining characteristics of austenitic stainless steel 304 through electric discharge machining. The effectiveness of the EDM process with stainless steel is evaluated in terms of the removal rate (MRR), the Tool Wear Rate (TWR) and the surface roughness of the work-piece produced. The experimental work is conducted utilizing Die Sinking electrical discharge machine of AQ55L model. Cylindrical copper electrode having a size of 019*37 mm and positive polarity for electrode (reverse polarity) is used to machine austenitic stainless steel 304 materials. The work material holds tensile strength of 580 and 290 MPa as yield strength. The size of the work-piece was 022*30 mm. Investigations indicate that increasing the peak current increases the MRR and the surface roughness. The TWR increases with peak ampere until 150 ja sec pulse-on time. From the experimental results no tool wear condition is noted for copper electrode at long pulse-on time with reverse polarity. The optimal pulse-on time is changed with high ampere.